The Sikh minority and the partition of the Punjab :1920-1947 - Chattopadhyay, Chhanda (Manohar, 2019)
Guru Nanak had gifted the Sikhs with an ideology. Guru Angad had given them the Gurmukhi script. Guru Arjan Dev coalesced the hymns authored or collected by the Gurus and made them a people of the book. Guru Govind Rai created the Khalsa identity with its five symbols (Panj Kakke). Maharaja Ranjit Singh's conquests gave them the pride of race. British insistence on recruiting only keshdhari Sikhs encouraged the Khalsa to assert their distinct identity. The trend accelerated since the revolt of 1857, when John Lawrence reversed the initial successes of the rebels with the recovery of Delhi with forces from the Punjab. Sikhs were co-opted by the British with the clever broadcast of the Guru Tegh Bahadur myth that the Sikhs would be able to avenge the martyrdom of the Guru in Delhi with the help of a white race. Since then the Sikhs formed the backbone of the British Indian army and all their political influence flowed out of this military connection. The unexpected Congress concession of weightage to the Muslims in the Lucknow Pact of 1916 awakened the Sikhs to the necessity of the defence of Khalsa interests. Their vociferations compelled the British to concede a 19 per cent weightage for the Sikhs in the Montagu-Chelmsford Act of 1919. Gandhi appreciated the indispensable nature of Sikh support for the success of the British military machine. His attempt to subsume the Akali movement under the umbrella of the Non-Cooperation movement in the 1920s against the British and again his attempt to win over the Sikhs for his Civil Disobedience movement during the Lahore Congress in 1929 reflected this shrewd political sense. Sikhs continued to wrench concessions both from the British and the Congress as long as the Pax Britannica had any chance of survival. But as the negotiations for decolonization quickened after the end of the Second World War, the magic of Sikh arms could no longer work miracles for their slender numbers. While British statesmen from Cripps to Attlee – all burnt gallons of midnight oil thinking of an acceptable settlement of the Hindu-Muslim impasse, no one paid much attention to the pathetic quest of Sikh leaders since 1940 to work out an acceptable formula for readjusting the borders of the Punjab to accommodate the birthplace of the Gurus or the canal colonies, worked through long years of Sikh toil.